Assessment of the biological consequences of controlling indoor solid fuel smoke emissions in Nepal - K.C., Binaya (2020)
Household air pollution (HAP) exposure and its consequences for human health have been a topic of interest in the medical and engineering research world for many years. Large populations in low and middle-income countries (LMICs) are exposed to HAP as a result of the combustion of solid biomass fuel, especially for household cooking. Short-term exposure to HAP may increase respiratory symptoms including cough and breathlessness, which on more prolonged exposure may cause serious respiratory damage and lead to premature death. Airway inflammation following exposure to inhaled pollutants is likely to be a key step in this process, and little is known about the mechanisms underlying responses to biomass smoke in human lung. The main aims of this thesis were to (i) quantify ‘real-life’ exposure to particulate matter of aerodynamic diameter smaller than 2.5 µm (PM2.5) and carbon monoxide (CO) measured during cooking on stoves in rural areas of Nepal in different geographical settings, (ii) assess the potential effect of biomass smoke extract generated in real life cooking on inflammatory responses in human lung tissue, and (iii) investigate the consequences of controlling biomass smoke exposure using improved cook stoves (with a flue to vent smoke out of the room) (ICS) on inflammatory responses in human lung tissue.